Non-suicidal self-injury among youth students during COVID-19 pandemic: the role of psychological factors in Jingzhou, China - Zhou, Lie; Yu, Ye; Liu, Bo; Zhou, Li-Fang; Sheng, Juan; Zhang, Xin-Feng; Deng, Xiao-Peng; Ran, Mao-Sheng (Frontiers in Psychiatry, 2024)
Objective This study aimed to explore the impact of the COVID-19 pandemic on non-suicidal self-injury (NSSI) among youth students, and the mediating role of psychological factors in the relationship between the COVID-19 pandemic and NSSI. Method An online survey was conducted at junior and senior high schools, as well as universities located in Jingzhou, Hubei Province, China between June 2021 and January 2022. The COVID-19 Impact Index was constructed using multiple correspondence analysis (MCA) method. The bootstrapping method was used for mediation analysis. Results A total of 16025 youth participated in the study and 12507 youth (78.1%) finished the questionnaires. The COVID-19 Impact Index had a significantly positive effect on NSSI (r=0.16, p<0.001). The mediation analysis results showed that the COVID-19 Impact Index had a significant indirect effect on youth’ NSSI (β=0.0918, 95% CI [0.0788, 0.1048]), and this indirect effect was mainly achieved through affecting youth’ anxiety, depression and post-traumatic stress disorder (PTSD). The mediation effect of anxiety on NSSI was 0.0584, the direct effect was 0.0334, and the mediation proportion was 63.6%. The mediation effect of depression on NSSI was 0.0668, the direct effect was 0.0250, and the mediation proportion was 72.8%. The mediation effect of PTSD on NSSI was 0.0640, the direct effect was 0.0278, and the mediation proportion was 69.7%. All the mediation effects, direct effects and total effects were statistically significant (p<0.001). Conclusion The higher the impact of the COVID-19 Impact Index, the higher the prevalence of NSSI among youth students. Anxiety, depression and PTSD had mediated the relationship between the COVID-19 Impact Index and NSSI. It is suggested that specific health policies, mental health services and interventions should be developed to reduce the NSSI and improve mental health status among youth students during the COVID-19 pandemic.